CMOS Cellular Receiver Front-Ends From Specification to Realization - Janssens, Johan. (The International Series in Engineering and Computer Science, 2002)
CMOS Cellular Receiver Front-Ends: from Specification to Realization deals with the design of the receive path of a highly-integrated CMOS cellular transceiver for the GSM-1800 cellular system. The complete design trajectory is covered, starting from the documents describing the standard down to the systematic development of CMOS receiver ICs that comply to the standard. The design of CMOS receivers is tackled at all abstraction levels: from architecture level, via circuit level, down to the device level, and the other way around. The theoretical core of the book discusses the fundamental and more advanced aspects of RF CMOS design. It focuses specifically on all aspects of the design of high-performance CMOS low-noise amplifiers.